2(3x+4)-3(x+1)=11

Simple and best practice solution for 2(3x+4)-3(x+1)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x+4)-3(x+1)=11 equation:


Simplifying
2(3x + 4) + -3(x + 1) = 11

Reorder the terms:
2(4 + 3x) + -3(x + 1) = 11
(4 * 2 + 3x * 2) + -3(x + 1) = 11
(8 + 6x) + -3(x + 1) = 11

Reorder the terms:
8 + 6x + -3(1 + x) = 11
8 + 6x + (1 * -3 + x * -3) = 11
8 + 6x + (-3 + -3x) = 11

Reorder the terms:
8 + -3 + 6x + -3x = 11

Combine like terms: 8 + -3 = 5
5 + 6x + -3x = 11

Combine like terms: 6x + -3x = 3x
5 + 3x = 11

Solving
5 + 3x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 3x = 11 + -5

Combine like terms: 5 + -5 = 0
0 + 3x = 11 + -5
3x = 11 + -5

Combine like terms: 11 + -5 = 6
3x = 6

Divide each side by '3'.
x = 2

Simplifying
x = 2

See similar equations:

| 17=9+2u | | -2+12-(-14)= | | 66w-50= | | 4(2x-3)-3(x-4)+7x=6 | | 77x+20=350 | | x^2+x-1=15x | | -14+23=-3(x+2) | | 2(3z+1)-(z-6)=18 | | -135+2x=52-9x | | .3x-.14x-.81=-.6x+.29 | | 66w+50= | | 9y+15=5y-5 | | X=2x-3+4 | | .3x-.14x-.81=-.6x+29 | | 6x-1=5+3x | | 2*12*40+5*18*40+3238+500= | | 2x-43=65 | | 33w+49-33w+1= | | 9+(-10)= | | 70=-14x | | 0.162+2.76= | | 6x-4+5=1 | | 2+11x+11K-3x-3k-9= | | -44-6n=4(-10-n) | | -8-0-(-16)-7+5= | | 6x^2+25x-24=0 | | 6y-11x=15 | | 15r^2-4r-4=0 | | -4=3b+b | | 2x+3-3x=7 | | (-4+-1x^2)=0 | | (2+5)*(12+18)*40+3238+500= |

Equations solver categories